Congenital chylothorax: a rare entity - Gandhi, Prachi; Malik, Sushma; Jamkar, Nilesh N.; Singh, Vinaya A.; Wade, Poonam (International Journal of Contemporary Pediatrics, 2020)
Pleural effusions in a neonate are generally congenital in about one third of the cases and acquired in the remaining two thirds. Congenital isolated pleural effusion is rare. It has an incidence of approximately 1 in 12000 to 1 in 15000 pregnancies. Chylothorax is the most common cause of neonatal congenital pleural effusion. Incidence of congenital chylothorax is 1 in 8600 to 1 in 10000 deliveries with a male to female ratio of 2:1. It poses both a diagnostic as well as therapeutic challenge to the neonatologist. Authors hereby present a rare case of congenital chylothorax which was medically managed and discharged. The neonate responded well to octreotide and medium chain triglyceride (MCT)-diet and was discharged without any complications.